Effects of postpartum body weight changes on subsequent reproductive performance in N'Dama cattle maintained under traditional husbandry systems - Agyemang, K.; Little, D.A.; Bah, M.L. (Elsevier, 1991)
Quantifies the effects of postpartum body weight changes on subsequent reproductive performance of N'Dama cattle managed under traditional husbandry systems in Gambia. Analysis of body weights from 4 months before conception to the month of conception showed that 71 percent of cows were gaining weight at a mean rate of 1.74 kg per month before conception. The results indicate that strategic supplementation of cows during the first 3 months after parturition either to maintain or to gain weight could lead to improved reproductive performance in village - managed animals.